Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set: 23

Answer

$\frac{-y-4}{y+3}$

Work Step by Step

$\frac{y+2}{y+3}$-2 =$\frac{y+2}{y+3}$-2 ($\frac{y+3}{y+3}$) =$\frac{y+2-2(y+3)}{y+3}$ =$\frac{y+2-2y-6}{y+3}$ =$\frac{y-2y+2-6}{y+3}$ =$\frac{-y-4}{y+3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.